ADP-glucose pyrophosphorylase large subunit 2 is essential for storage substance accumulation and subunit interactions in rice endosperm. (August 2016) - Tang, Xiao-Jie; Peng, Cheng; Zhang, Jie; Cai, Yue; You, Xiao-Man; Kong, Fei; Yan, Hai-Gang; Wang, Guo-Xiang; Wang, Liang; Jin, Jie; Chen, Wei-Wei; Chen, Xin-Gang; et al.
Highlights: The mutation in OsAGPL2 resulted in aberrant storage substances in the w24 endosperm. Expression of AGPase, activities of Pho1 and SuSy were enhanced in the w24 endosperm. Expression of OsAGPL2 and OsAGPS2b was highly coordinated in rice endosperm. Direct interactions of OsAGPL1:OsAGPS1 as well as OsAGPS2b:OsAGPL2 were verified. Self-binding was evident for the OsAGPL2 subunits but not the OsAGPS2b subunits. Abstract: ADP-glucose pyrophosphorylase (AGPase) controls a rate-limiting step in the starch biosynthetic pathway in higher plants. Here we isolated a shrunken rice mutant w24 . Map-based cloning identified OsAGPL2, a large subunit of the cytosolic AGPase in rice endosperm, as the gene responsible for the w24 mutation. In addition to severe inhibition of starch synthesis and significant accumulation of sugar, the w24 endosperm showed obvious defects in compound granule formation and storage protein synthesis. The defect in OsAGPL2 enhanced the expression levels of the AGPase family. Meanwhile, the elevated activities of starch phosphorylase 1 and sucrose synthase in the w24 endosperm might possibly partly account for the residual starch content in the mutant seeds. Moreover, the expression of OsAGPL2 and its counterpart, OsAGPS2b, was highly coordinated in rice endosperm. Yeast two-hybrid and BiFC assays verified direct interactions between OsAGPL2 and OsAGPS2b as well as OsAGPL1 and OsAGPS1, supporting the model for spatiotemporal complex formation of AGPase isoforms in rice endosperm. Besides, our data provided no evidence for the self-binding of OsAGPS2b, implying that OsAGPS2b might not interact to form higher molecular mass aggregates in the absence of OsAGPL2. Therefore, the molecular mechanism of rice AGPase assembly might differ from that of Arabidopsis .